Associations between children's diet quality and watching television during meal or snack consumption: A systematic review - Avery, Amanda; Anderson, Catherine; McCullough, Fiona (Maternal and child nutrition, 2017)
Studies have identified an association between watching television (TV) and childhood obesity. This review adds context to existing research by examining the associations between TV viewing, whilst eating, and children's diet quality. Web of Science and PubMed databases were searched from January 2000 to June 2014. Cross‐sectional trials of case control or cohort studies, which included baseline data, measuring the associations between eating whilst watching TV and children's food and drink intake. Quality of selected papers was assessed. Thirteen studies, representing 61,674 children aged 1–18 yrs, met inclusion criteria. Of six studies reporting overall food habits, all found a positive association between TV viewing and consumption of pizza, fried foods, sweets, and snacks. Of eight studies looking at fruit and vegetable consumption, seven identified a negative association with eating whilst watching TV (p < .0001). Four out of five studies identified a positive association between watching TV whilst eating and servings of sugar‐sweetened beverages (p < .0001). Four studies identified an association between low socioeconomic status and increased likelihood of eating whilst watching TV (p ≤ .01). Family meals did not overcome the adverse impact on diet quality of having the TV on at mealtimes. Eating whilst watching television is associated with poorer diet quality among children, including more frequent consumption of sugar‐sweetened beverages and high‐fat, high‐sugar foods and fewer fruits and vegetables. Although these differences in consumption are small, the cumulative effect may contribute to the positive association between eating whilst watching TV and childhood obesity.